(untitled) (The Planet, 2022)
Introduction: Systemic lupus erythematosus (SLE) is a multi-system autoimmune disease exhibiting diverse clinicopathological manifestations. Renal involvement [lupus nephritis (LN)] occurs in a maximum of these patients during the disease, accounting for significant morbidity and mortality. LN exhibits diverse clinical features with variable glomerular histopathological patterns. The class of LN discerned on renal biopsy evaluation highly correlates with prognosis and guides appropriate therapeutic management. Prompt institution of immunosuppressive therapy, as determined by the renal pathologic lesion, results in favorable outcomes with better renal survival rates. Aim of the study: The study aimed to correlate the clinico-demographic findings and laboratory parameters of lupus nephritis with the histopathological patterns. Methods: This was a cross-sectional observational study conducted among thirty patients with lupus nephritis, admitted into the department of Medicine, Rangpur Medical College and Hospital, from January 2014 to December 2015. The sample was collected by the purposive sampling technique. Diagnosis of SLE was done on the basis of the American College of Rheumatological Criteria (ACR). After written consent from the patients, all patients were undergone renal biopsy and tissue was analyzed for histopathological examination. Data were processed and analyzed with the help of the computer program SPSS and Microsoft excel. Quantitative data are expressed as mean and standard deviation and qualitative data as frequency and percentage. Comparisons were done by tabulation and graphical presentation in the form of tables, pie charts, graphs, bar diagrams, histograms, charts, etc. Result: Among the thirty patients found to have lupus nephritis, female 27(90%) were predominance and 17(56.66%) of the patients were of childbearing age between 21 and 40 years, the mean age of the study patient was 25.16 ± 8.35 (SD) years. The most frequent clinical features were arthritis (93.33%), fever (80%), oral ulceration (66.66%), edema (66.66%), and hypertension (46.66%). Renal impairment was present in 12(40%) patients. Anti-ds DNA was positive (86.66%) in patients and antinuclear antibody (ANA) was positive (96.66%), 27 patients (90.0%) had low complement (C3 and C4) levels. Among all patients, 7 (23.3%) had ≥3 gram/day proteinuria. The common histological type was found in class IV, which was 14(46.66%), Class III, 8(26.66%) patients, and Class V, 6(20%) patients. Conclusion: Lupus nephritis (LN) is one of the serious manifestations of systemic lupus erythematosus (SLE). Despite great improvement in the management of lupus nephritis, it remains the most frequent cause of SLE-related mortality. It has diversities of clinical and histological presentations.